Disordered eating behaviors and psychological correlates. Data from the Ensanut 2018-19 - Claudia Unikel-Santoncini; Ietza Bojorquez-Chapela; María I Hernández-Serrato; Aremis Villalobos-Hernández (Instituto Nacional de Salud Pública, 2022)
Objective. To analyze the relationship between disordered eating behaviors (DEB) and depressive symptoms, suicide attempts, and alcohol and tobacco use in adolescents in a national survey in Mexico. Materials and methods. Data from the Encuesta Nacional de Salud y Nutrición 2018-19 were used. Three levels of DEB were established: no risk (DEB-NR), moderate risk (DEB-MR), and high risk (DEB-HR). An ordinal logistic regression model was performed with level of DEB risk as a dependent variable. Results. National prevalence of DEB-MR was 6.0% (95%CI: 5.6, 6.5), while that of DEB-HR was 1.3% (95%CI: 1.1, 1.6). Suicide attempt (OR= 1.82, 95%CI: 1.02,3.25) and depressive symptoms (OR= 2.6, 95%CI: 1.40,4.98) were associated with being at a higher risk of DEB. Conclusion. Since both depressive symptoms and suicide attempt are associated with DEB, prevention strategies should consider interventions that simultaneously address the various mental health problems present in adolescence.